Construction site security - Arata, Michael J. (McGraw Hill, 2006)
In order to meet insurance requirements or earn incentives, construction companies must now put a security plan in place for every construction site. This comprehensive resource covers all the essentials of planning, prioritizing, and implementing construction site security.